Semi Solid Casting of Aluminum Alloy Using a Cooling Slope Technic. - Hawzheen Abdulwahid Ibrahim; Mohammadtaher M. Saeed Mulapeer (Zanco Journal of Pure and Applied Sciences, 2020)
In this study, semi-solid metal casting technology has been used to make castings from Al alloy 6063 scrap using different casting temperatures and a cooling slope of 30cm long. The purpose of the cooling slope was to cool down the liquid metal into a semi-solid state of about 60% liquid before entering the mold. The results showed that the semi-solid metal cast samples that pass over a cooling slope had higher strength and ductility as compared to the traditional direct casted samples due to the evolution of microstructure from dendritic into globular morphology. A ductility increase over 38%, 100%, and 34% is recorded for semi-solid casting over a cooling slope compared to direct casting for liquid metal at 750oC, 800oC, and 900oC respectively. Strength is improved by about 8% for semi-solid casting at 750 and 900oC compared to direct casting. For 800oC no improvement is recorded in terms of the tensile strength for cooling slope over direct casting